Improving the communication path reliability of WiMAX mesh network using multi sponsor technique - Afzali, Mahboubeh (Kluwer Academic Publishers, 2015)
Recently Worldwide Interoperability for Microwave Access (WiMAX) mesh network has emerged as a promising wireless technology in order to enable fast, cost-effective network deployment. However, achieving these requirements is a daunting task due to the mesh subscriber station failures in the presence of the adversarial environment. In fact, mesh subscriber station failure is one of the important challenges in satisfying the requirements of the communication path in the WiMAX mesh network. To cope with the node failures during communication path bypassing the intermediate nodes, the enhancement of communication path reliability is of the utmost importance in the WiMAX mesh network. In this paper, a new technique based on multi sponsor nodes is presented to enhance the reliability of the multi hop communication path. Markov model based on the multi sponsor nodes is also applied to enhance the communication path reliability when the network face with malfunctioning nodes. Ultimately, a generic model based on the stochastic attribution of WiMAX mesh network is developed to measure the reliability of the multi hop communication path. Consequently, multi sponsor technique in WiMAX could more thoroughly improve the reliability of the communication path in the WiMAX mesh network.